2018
DOI: 10.9734/ajaees/2018/45205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Security on Household’s Agricultural Productivity in Benin

Abstract: This paper aims at studying the impact of land tenure on household's agricultural productivity in Benin. Data used in this study come from EMICOV (Enquête Modulaire Intégrée sur les Conditions de Vie des Ménages) collected in 2012 and covered 626 Benin's farming households. The method used is the Conditional Mixed Process (CMP) technic approach. Results show that land certificate ownership increases by 0.238 the likelihood of investing in agricultural equipment whereas the customary law ownership increases thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Place and Hazell (1993) found that with few exceptions traditional land rights do not have signi cant effects on agricultural investments. In contrast, Sossou and Mbaye (2018) showed that customary law ownership increases the likelihood of investing in agricultural equipment compared to households with no land ownership.…”
Section: Introductionmentioning
confidence: 94%
“…Place and Hazell (1993) found that with few exceptions traditional land rights do not have signi cant effects on agricultural investments. In contrast, Sossou and Mbaye (2018) showed that customary law ownership increases the likelihood of investing in agricultural equipment compared to households with no land ownership.…”
Section: Introductionmentioning
confidence: 94%
“…Land tenure stability facilitates farmers' adoption of CCB via land mortgage loans. Stable land tenure, evidenced by long-term land contract rights certification, empowers farmers to diminish credit evaluation costs with banks and thereby secure credit funds through land mortgages [71]. These credit funds, in turn, increase the likelihood of farmers making protective investments in their land [44], which further encourages CCB adoption.…”
Section: Mechanism Analysismentioning
confidence: 99%